Halusinasi Terhadap Hantu Dalam Karya Lukis Surealisme - Novriadi Novriadi (Lembaga Pengembangan Kinerja Dosen, 2024)
Based on the scientific consensus, ghosts are not a scientifically valid concept. Their existence cannot be explained. Even though it has been investigated for centuries, there is not a single piece of scientific evidence that shows that a place can be inhabited by the spirits of the dead. In Islam there is no such thing as a ghost, Islam calls them jinn, devils and demons. Of the many types of ghosts, the one most feared by people is the ghost of the dead. Some ordinary people think that ghosts are the spirits of dead people who wander around, especially curious dead people whose spirits are trapped in the natural world. The fact that ghosts are the incarnations of dead people cannot be justified. Islam does not reject the existence of spirits, in fact supernatural matters such as the existence of spirits must be believed because the Pillars of Faith themselves consist of supernatural things that must be believed in.